Chapter 30: Lettuce, Endive, Escarole Production in Florida - William M. Stall; Richard N. Raid; Susan E. Webb (EDIS, 2019)
This document is HS728, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.